Human milk : sampling and measurement of energy-yielding nutrients and other macromolecules - McGuire, Michelle (Michelle Kay); O'Connor, Deborah (Academic Press, 2021)
Human Milk: Sampling and Measurement of Energy-Yielding Nutrients and Other Macromolecules presents comprehensive, rigorous, state-of-the-science information on the origins, analysis, concentrations and variation in energy-yielding nutrients and other macromolecules present in human milk. The book includes information on how best to collect and store milk for determining concentrations of these important milk constituents and considers how to conduct milk composition analysis in research, clinical and resource-poor settings. Written by a group of international experts who are actively conducting research related to human milk macronutrients, each chapter also provides cutting-edge rationale for what research is still needed in this evolving field. In addition, the book also outlines challenges and opportunities faced by clinicians, industry leaders and regulators interested in adding these components to infant foods, human milk nutrient fortifier and formula.